Why Men Have Abortions: Quantitative and Qualitative Perspectives From Urban Family Planning Clinics in Chicago, Illinois, USA - Jenna M. Heath; Brian T. Nguyen (American Journal of Men's Health)
Support for abortion is comparable between men and women in the United States; one in five reproductive age men reports abortion involvement. Yet, societal focus on abortion as a uniquely women’s issue minimizes men’s involvement in abortion. We conducted a secondary analysis of survey ( n  = 203) and interview data ( n  = 30) on male partner’s experiences accompanying abortion recipients at two family planning clinics in Chicago, Illinois. Respondents identified reasons for abortion from a prepopulated 14-item list. We correlated reasons with respondent’s abortion preference and decision satisfaction, characterizing this relationship via thematic analyses of interview transcripts. Nearly all men (97.5%) identified multiple reasons for abortion (median: 6/14), including: mistimed pregnancy (80%), impact on his/his partner’s education/career (75%–80%), and finances (71%). Neither individual reasons nor number of reasons was significantly associated with abortion decision preference or decision satisfaction. While 41% would not have chosen abortion, only 10% reported dissatisfaction. Men’s perception of decision concordance with their partner was significantly linked to their satisfaction ( p < .01). Thematic analysis highlighted complex partner involvement, including shared and deferred decision-making and tension amid demonstrated support. Many abortion-accompanying men preferred to continue the pregnancy, yet very few reported dissatisfaction with the ultimate decision, which may be related to perceived decision concordance with their female partner. Men’s decisions for abortion are complex and include varying degrees of male partner involvement and/or decision deferral to female partners.